Justifying strict liability : a comparative analysis in legal reasoning - Cappelletti, Marco, 1986- (Oxford : Oxford University Press, 2023)
The imposition of strict liability in tort law is controversial, and its theoretical foundations are the object of vigorous debate. Why do or should we impose strict liability on employers for the torts committed by their employees, or on a person for the harm caused by their children, animals, activities, or things? In responding to this type of questions, legal actors rely on a wide variety of justifications. This book explores, in a comparative perspective, the most significant arguments that are put forward to justify the imposition of strict liability in four legal systems, two common law, England and the United States, and two civil law, France and Italy.
Also issued in print: 2022.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on February 2, 2023).
Keywords: Strict liability -- England; Strict liability -- United States; Strict liability -- France; Strict liability -- Italy; Law -- Methodology; Comparative law; Law; Laws of specific jurisdictions & specific areas of law